PENGARUH LIVE STREAMING, ONLINE REVIEW CUSTOMER DAN INFLUENCER MARKETING TERHADAP MINAT BELI PADA APLIKASI TIKTOK SHOP (Studi Pada Mahasiswa Universitas Islam Darul Ulum Lamongan): PENGARUH LIVE STREAMING, ONLINE REVIEW CUSTOMER DAN INFLUENCER MARKETING TERHADAP MINAT BELI PADA APLIKASI TIKTOK SHOP (Studi Pada Mahasiswa Universitas Islam Darul Ulum Lamongan) - Sundari, Ariefah; NASIKHIN, MUH. NUR ALI KHOIRUN (Applied Research in Management and Business, 2024)
This research aims to determine the influence of live streaming, online customer reviews and influencer marketing on consumer buying interest in the TikTok Shop application. This research was conducted at the Darul Ulum Lamongan Islamic University involving 98 students as respondents. This research uses the Purposive Sampling method. The research was carried out with partial tests and simultaneous tests using SPSS 26. The results of the coefficient of determination test based on the R Square value show that live streaming, online customer reviews and influencer marketing on consumer buying interest are 42.6%.From the analysis results obtained, the partial test results of the live streaming variable have a positive and significant influence on consumer buying interest with tcount (3.212) > ttable (1,984) with sig 0.002 < 0, 05. The online customer review variable has no effect on consumer buying interest with tcount (1.023) < t table (1,984) with sig 0.309 > 0.05. The influencer marketing variable has a positive and significant influence on consumer buying interest with tcount (4.704) > ttable (1,984) with sig 0.000 < 0.05. Based on the simultaneous F test, it can be seen that Fcount (23.507) > Ftable (2.70). It can be stated that simultaneously live streaming, online customer reviews and influencer marketing influence consumer buying interest.